2016
DOI: 10.1123/jpah.2015-0708
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Objectively Measured Physical Activity and Development of Executive Functioning Across the Transition to First Grade

Abstract: The development of the visuospatial sketchpad (working memory), the central executive (working memory), and fluency (cognitive flexibility) might be improved by increasing the amount of time being physically active. However, as other subcomponents of executive functioning were not affected, the role of other aspects of physical activity, such as intensity and content, in the development of executive functions should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The cognitive flexibility and planning tasks used by Booth et al 12 and van der Niet et al 13 would require greater upregulation of cognitive control because these tasks necessitate the integration of inhibition and working memory. Conversely, when inhibitory control was specifically considered, null associations were observed across several measures, including a flanker task,15, 81 Stroop task, 13 Go/NoGo, 81 and the Stop Signal Task 16 . Thus, our null results in relation to behavioral measures of inhibitory control align with these previous findings.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The cognitive flexibility and planning tasks used by Booth et al 12 and van der Niet et al 13 would require greater upregulation of cognitive control because these tasks necessitate the integration of inhibition and working memory. Conversely, when inhibitory control was specifically considered, null associations were observed across several measures, including a flanker task,15, 81 Stroop task, 13 Go/NoGo, 81 and the Stop Signal Task 16 . Thus, our null results in relation to behavioral measures of inhibitory control align with these previous findings.…”
Section: Discussionsupporting
confidence: 84%
“…Likewise, daily MVPA was generally not related to cognitive control. Previous studies on objectively measured daily PA and cognitive control focused primarily on MVPA and reported mixed findings 12, 13, 14, 15, 16, 17, 18 , 81 . When it was included in the analyses, daily VPA was not related to selective attention 14 or impulse control 17 in adolescents.…”
Section: Discussionmentioning
confidence: 88%
“…The supposed association between a fit body and a fit brain in children only enhances the relevance of children's PA programmes. However, although a positive association between PA and cognitive performance in children is considered to be established, the available literature remains inconsistent (Best, ; Bidzan‐Bluma & Lipowska, ; Diamond & Ling, ; Donnelly et al, ; Vandenbroucke, Seghers, Verschueren, Wijtzes, & Baeyens, ). In particular, the underlying mechanisms are still debated.…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous studies revealed a positive relation between regular PA or exercise and performance in different cognitive tasks in children, especially for cognitive control and WM performance [46, 47, 53, 54]. As mentioned above, PA positively modulates brain functions and structures, as well as behavioral aspects of cognition [55].…”
Section: Introductionmentioning
confidence: 99%